Drugs in pregnancy. (April 2020) - Andersen, Jon T.; Futtrup, Tina Bergmann
Abstract : Summary: Since the thalidomide scandal in the 1960's use of drugs in pregnancy has often been associated with great uncertainty, it can affect both the mother and the fetus. However, the concern may mistakenly lead to nonharmful drugs being attributed teratogenic effects. The drug use during pregnancy and the safety of the most commonly used drugs are in the following being discussed. Furthermore, a practical guide to risk assessment and considerations when initiating a drug treatment is presented.